Spatial accessibility analysis of green space from a health-benefit perspective: Implications for healthy urban development - Wei, Xiangrui; Zhao, Chunrong; Yan, Li; Fu, Juanlin; Bao, Ying; Liu, Xiao (Frontiers in Ecology and Evolution, 2022)
The spatial accessibility of urban park green space (UPGS) plays a crucial role in promoting the healthy development of cities and their residents. However, previous studies have overestimated the accessibility of UPGS and failed to adequately consider the impact of variegated parks on residents’ needs. To fill this gap in the research, we first propose an improved two-step floating catchment area (Huff-2SFCA) method that takes into consideration the trade-offs between supply, demand, and walking time to calculate the UPGS accessibility index for the built-up area of Mianyang, China. Next, we assess the spatial characteristics of UPGS accessibility from both partial and overall points of view and further explore the relationship between accessibility and population size. Our results show that (1) every street area has a different form of UPGS construction, and most of these spaces are of poor quality; (2) municipal-level parks are significantly more accessible than district-level parks, community-level parks, or neighborhood-level parks; (3) the overall distribution of accessibility is generally characterized by a decreasing trend along both sides of the river, with poor overall accessibility; and (4) 243 residential districts are located in high-demand–low-supply areas that need improving. This study can be employed to identify areas that are underserved by UPGS and can provide a basis for improving the accessibility of UPGS and promoting its health benefits.